PENDIDIKAN KARAKTER BAGI ANAK USIA SEKOLAH DASAR MELALUI SEMIOTIK GERAK TARI BESKALAN - Nita, Cicilia Ika Rahayu; Rahayu, Sri (Universitas Pendidikan Indonesia, 2014)
The purpose of this research detailed as follows: describe the optimization of the formation of character values in school age children through dance Beskalan semiotic in Malang derby dance studio, dance semiotic determine the influence that proxy Beskalan into Dimension Icon, Index and Dimensions symbol of the establishment character values in school age children Dancing in Malang, knowing the dimensions of the most influential on the formation of character values in school age children in the dance studio in the city of Malang. Test the hypothesis that the function t test is used to determine the effect of partially between the independent variable (x) with variable (y). To determine the effect of simultaneously between the dependent variable with the independent variable F. Both trials used the t test and F test used 5% significance level. Researchers used a serial computer with SPSS 18 for windows to perform hypothesis testing.Keywords: character, semiotik, dance, beskalan, value.